LEGAL CONSEQUENCES OF LIMITED LIABILITY COMPANIES OBTAINING BANKRUPTCY DECISIONS - Kurniawan, Nico Theo (UNISSULA Semarang, 2024)
The purpose of this study is to determine and analyze the Legal Consequences of Limited Liability Companies After Bankruptcy Decisions. This study uses a normative legal approach, with a descriptive analytical research method. Based on the study, it is concluded that bankruptcy decisions on Limited Liability Companies have broad impacts that include cessation of business activities, management and distribution of assets, obligations to creditors, and dissolution of the company. During the bankruptcy process, the role of the curator is very important in ensuring that all obligations are met fairly and in accordance with the law. Shareholders and managers must also pay attention to the legal impact of the bankruptcy process, including their possible legal liability.